Ralph Waldo Emerson in Context - Mott, Wesley T. (Cambridge : Cambridge University Press, 2013)
This collection of newly commissioned essays maps the vital contextual backgrounds to Ralph Waldo Emerson's life and work. The volume begins with a detailed chronology of Emerson's life and publishing history, setting the stage for a wide-ranging discussion of his geographic and environmental contexts from early and later life, including his travels and intellectual encounters with the United States, Europe and Asia. It goes on to survey the intellectual terrain of the nineteenth century, exploring Emerson's relationship with key philosophical, aesthetic, theological, scientific, familial, social and political contexts and issues. Finally, it assesses the popular and critical receptions that have solidified Emerson's legacy as a towering figure in American literature, criticism and culture today. Fans, students and scholars will turn to this reference time and again for a fuller understanding of this seminal American writer.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).